IMPLEMENTASI ENVIRONMENTAL SUPPORT PROGRAMME PHASE III (ESP3) DENMARK DI HUTAN HARAPAN (JAMBI DAN SUMATERA SELATAN) INDONESIA TAHUN 2013-2018 - Sri Wulandari; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain about the Implementation of Denmark Environmental Support Programme phase III (ESP3) in Harapan Rainforest (Jambi Province and South Sumatera Province). ESP3 is the third Environmental Support Programme implemented in Indonesia by Government of Indonesia and Government of Denmark (DANIDA) and Harapan Rainforest is the first forest in Indonesia to be managed under an ‘Ecosystem Restoration’ License which mandate the concession holders to manage the forest for restoration instead of logging. This research uses the Perspective of Green, the level of analysis of nation states, Theory of International Cooperation and the concept of Sustainable Development Goals. The method used is a qualitative research method. This analysis is based on data obtained from literature studies. Writer uses data drawn from collection of Journals, Book, and Internet. The results of the research in this paper are implementation of ESP3 in Harapan Rainforest (2013-2018) is with support from DANIDA to Harapan Rainforest in the form of technical support and funding grant. The support Danida to Harapan Rainforest is for helping infrastructure, Forest and biodiversity Restoration, agroforesty practices, research and development, law enforcement, collaborations with communities borders and support for Batin Sembilan communityKeyword : Environmental Support Programme phase III (ESP3), Danish International Development Agency (DANIDA), Harapan Rainforest.